DETERMINANTS OF ISLAMIC DIGITAL WALLET ACCEPTANCE AMONG URBAN MUSLIM YOUTH: INTEGRATING TAM, TPB, AND RELIGIOSITY - Hanifiyah Yuliatul Hijriah; Kafiyla Sekar Sidhi Parahita; Dahlia Bonang; Himmatul Kholidah; Aqilah Nadiah Md Sahiq; Hanif Fadhlillah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2026)
Islamic digital wallets require distinct scholarly attention from conventional digital wallets because their adoption is not only shaped by technological convenience, but also by religious values, Sharia compliance, and users’ perceptions of Islamic financial practices. However, empirical studies on Islamic e-wallet adoption remain limited, particularly those integrating by integrating the Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB), and religiosity among Muslim youth in urban Indonesia. This research examines the factors that influence the intention of urban Muslim youth to use Islamic digital wallets. Using a quantitative methodology, the study collected data from 100 respondents through purposive sampling. Muslim Generation Z users of Islamic e-wallets in Surabaya City were specifically targeted via an online survey. Data analysis was conducted with multiple linear regression in SPSS Version 29. The results reveal that perceived usefulness, perceived ease of use, religiosity, attitude toward behavior, and perceived behavioral control have a significant and positive effect on the intention to use Islamic e-wallets, while subjective norm shows a significant negative effect on adoption intention. The study asserts that Islamic digital wallet adoption should be understood as a multidimensional phenomenon that combines digital service quality, behavioral intention, and faith-based financial values, with broader implications for strengthening Islamic digital finance and advancing inclusive Sharia-compliant financial services.